Sono-crystallization kinetics of K2SO4: Estimation of nucleation, growth, breakage and agglomeration kinetics - Bari A.H.; Chawla A.; Pandit A.B. (My University, 2025)
Application of ultrasound in crystallization has showed improved process characteristics. Although several attempts have been made in the past to study the sono-crystallization kinetics, only nucleation and crystal growth were considered, neglecting breakage and agglomeration of crystals. In this study, an attempt is made for the estimation of the kinetic parameters of all the phenomena occurring simultaneously during sono-crystallization. For this, both conventional and ultrasonic crystallization of K2SO4-water system has been reported. Sono-crystallization experiments were carried out using ultrasonic horn operating at 20 kHz frequency. Reduction in the induction time, reduction in metastable zone width (MSZW), narrowing of crystal size distribution (CSD) were the key observations of sono-crystallization experiments. Population balance equations (PBE) were used to model the crystallization system and the various kinetic parameters have been estimated. The kinetic parameters obtained for conventional crystallization and sonocrystallization were compared. The estimated parameters suggest an increase in nucleation and breakage rate during sono-crystallization. Growth rates were observed to be of the same order of magnitude for both conventional and sonocrystallization. While agglomeration during sono-crystallization was found to be negligible. © 2016 Elsevier B.V.